Hydration properties of belite cement prepared by lime-hydrothermal treatment of Saudi basaltic volcanic ash and glass - Tamer H. A. Hasanin; Alaa Muqbil Alsirhani; Mahmoud A.A. Ibrahim; Yogesh K. Ahlawat; M. A. Tantawy (Scientific Reports)
Abstract In this study, lime, volcanic ash, glass, and OPC were used to prepare belite, belite/OPC blended, and volcanic ash/OPC blended cements. The hydrothermal treatment of volcanic ash/lime mixes at 190 °C for 3.5 h followed by calcination at 600 °C for 3 h. The heat of hydration of cements was measured, and hydration characteristics were assessed by combined water, compressive strength, bulk density, and total porosity measurements. The microstructural changes with hydration progress were monitored by XRD, TGA, FTIR, and SEM techniques. Hydrated calcium silicate is formed by hydrothermal treatment and was transformed to belite by calcination. The heat of hydration of plain belite cements increases with increasing lime content, confirming its unsuitability for massive concrete applications. Whereas, belite/OPC blended cements exhibit a lower heat of hydration to be suitable for applications requiring moderate heat of hydration and low initial strength gain. The rate of hydration of belite cement improves both by increasing the content of lime to 25–30% as well as blending with OPC. Volcanic ash/OPC blended cement has an average compressive strength between plain belite cement and belite/OPC blended cement. This research provides valuable insights for practical application of prepared belite cement in the construction.